PENGGUNAAN MEDIA BIG BOOK UNTUK MENINGKATKAN KETERAMPILAN MEMBACA KALIMAT SEDERHANA - Hilda Hadian, Latifah; Mochamad Hadad, Sugara; Marlina, Ina (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2018)
This research is motivated by minimal reading skills, so it can affect children's academic and psychological achievements. Psychological problems that arise due to the lack of initial reading skills, namely when working on tasks related to reading children interfere with friends by talking, making noise when friends do tasks, not completing assignments, refusing when asked to do very long tasks, especially tasks that have a lot of reading, difficulties when receiving long instructions, not thorough and in a hurry when doing tasks. Based on the results of observations in the field the researchers looked at the methods and models used by the teacher when the reading learning process was quite appropriate, but in the learning process they did not provide a picture or media of learning that could help understanding and attract children's attention. One alternative learning media that can be used in the learning of early reading especially reading simple sentences is with the use of Big Book media. This media is considered suitable for early reading learning because it adheres to the principle of general language science. The research method used was PTK, with research subjects of class II SD Negeri Rahayu Subang totaling 17 students. In general, the activities of class II students in learning Indonesian about the skills of reading simple sentences using Big Book media experienced positive developments, and there were improvements in the ability to read simple sentences.